Disentangling the Dynamic Digital Capability, Digital Transformation, and Organizational Performance Relationships in Smes: a Configurational Analysis Based on Fsqca - Saunila, Minna; Karadağ, Hande; Şahin, Faruk; Karamollaoğlu, Nazlı (Springer, 2024)
While digitalization has become inevitable for firms of every size, a limited number of studies to date aimed to investigate the impact of digital capabilities and digital transformation on the organizational performance of small businesses. Drawing on the dynamic capabilities view, the current study analyzes the conditions under which the dynamic digital capability of a small and medium-sized enterprise (SME) would lead to higher performance. In this study, a unique fuzzy-set qualitative comparative analysis methodology was used for analyzing the data collected from 136 SMEs for investigating the IT utilization, human capital, digital maturity, and digitalization strategy antecedents of dynamic digital capability. The results reveal that two particular configurations of dynamic digital capability are identified as the main digitalization influencers of organizational performance in SMEs. To the best of our knowledge, this study presents the first empirical findings to the literature about dynamic digital capability and organizational performance relationships in SMEs through the utilization of configurational analysis methodology. Theoretically, the study addresses an acknowledged need for a holistic approach to uncover the underlying mechanisms of dynamic digital capability formation and digital transformation in small firms, with their impact on firm performance. The findings also present vital practical implications for business owners, policy-makers, and bodies responsible for SMEs, by providing new insights about the combination of factors that drive high performance, particularly at times of turbulence, in these units.
Keywords: Dynamic digital capability; Digital transformation; Small to medium-sized enterprises; Organizational innovation; Configurational approach; Fsqca